Electroencephalographic Features of Convulsive Epilepsy in Africa: A Multicentre Study of Prevalence, Pattern and Associated Factors - Kariuki, Symon M.; White, Steven; Chengo, Eddie; Wagner, Ryan G.; Ae-Ngibise, Kenneth A.; Mwesige, Angelina Kakooza; Masanja, Honorati; Ngugi, Anthony K.; Sander, Josemir W.; Neville, Brian G.; Newton, Charles R. (Clinical Neurophysiology, 2016)
We investigated the prevalence and pattern of electroencephalographic (EEG) features of epilepsy and the associated factors in Africans with active convulsive epilepsy (ACE).We characterized electroencephalographic features and determined associated factors in a sample of people with ACE in five African sites. Mixed-effects modified Poisson regression model was used to determine factors associated with abnormal EEGs.Recordings were performed on 1426 people of whom 751 (53%) had abnormal EEGs, being an adjusted prevalence of 2.7 (95% confidence interval (95% CI), 2.5–2.9) per 1000. 52% of the abnormal EEG had focal features (75% with temporal lobe involvement). The frequency and pattern of changes differed with site. Abnormal EEGs were associated with adverse perinatal events (risk ratio (RR)=1.19 (95% CI, 1.07–1.33)), cognitive impairments (RR=1.50 (95% CI, 1.30–1.73)), use of anti-epileptic drugs (RR=1.25 (95% CI, 1.05–1.49)), focal seizures (RR=1.09 (95% CI, 1.00–1.19)) and seizure frequency (RR=1.18 (95% CI, 1.10–1.26) for daily seizures; RR=1.22 (95% CI, 1.10–1.35) for weekly seizures and RR=1.15 (95% CI, 1.03–1.28) for monthly seizures)).EEG abnormalities are common in Africans with epilepsy and are associated with preventable risk factors.EEG is helpful in identifying focal epilepsy in Africa, where timing of focal aetiologies is problematic and there is a lack of neuroimaging services.
Keywords: Electroencephalographic features; Active convulsive epilepsy; Risk factors; Africa